Correlation of Serum Erythropoietin and Ferritin Levels with the Frequency of Blood Donation - Uday Younis, Hussein; Fouz AA, Abdul Aziz; Norhaza, A Rahim
Aim: The objective is to assess the correlation of serum ferritin and erythropoietin levels with the frequency of donation among blood donors in Pulau Penang, Malaysia. Methods: One hundred and forty-seven (108 male and 39 female) voluntary whole blood donors whom donating blood at the Blood bank, Hospital Pulau Pinang were included. For each donor, haemoglobin, serum ferritin and erythropoietin (EPO) assay were done. Laboratory works had been done at the Advanced Diagnostic Laboratories (ADL), Advanced Medical and Dental Institute (AMDI), Universiti Sains Malaysia (USM). Results: A significantly increased (p=0.014) serum ferritin was found in the first time donor (105.3 ng/ml) compared to regular donors (69.3 ng/ml) who had donate blood more than once in the preceding year of both gender. The larger amount of donated blood in regular male donor results in a more risk of latent iron deficiency compared to female counterpart. EPO was significantly higher while ferritin was significantly lower in regular donors than in the control. The serum EPO showed a statistically significant inverse relationship with ferritin level and this relationship was significantly correlated. Conclusion: Adequate daily, oral iron supplementation at post donation would need to be provided for 90 days, which is longer than most current recommended iron replenishment programs together with the introduction of serum ferritin assay at first donation and annually for regular donors to increase the safety of national blood supply recommended.